Transfer Pricing Methods for Services and the Policy of Fixed Length Principle - Challoumis Constantinos (Economics and Business)
The paper deals with the methods used by companies for controlled transactions in services. The author performs an analysis of the ways a company that takes part in controlled transactions of transfer pricing can tackle tax issues using an adequate tax method. Services should comply with the arm’s length principle. Therefore, the best method rule and the comparability analysis have a critical role in the arm’s length principle of services. The paper compares the results of transfer pricing services with the transfer pricing of goods to conclude the similarities. The object of the paper is to determine the importance of the application of fixed length principle, meaning the application of additional tax for controlled transactions and declined tax for uncontrolled transactions. Therefore, this scrutiny showed that the unstable tax environments force enterprises to proceed to controlled transactions.